Corpus callosum atrophy is associated with mental slowing and executive deficits in subjects with age-related white matter hyperintensities: the LADIS Study. Issue 5 (6th October 2006) - Jokinen, Hanna; Ryberg, Charlotte; Kalska, Hely; Ylikoski, Raija; Rostrup, Egill; Stegmann, Mikkel B; Waldemar, Gunhild; Madureira, Sofia; Ferro, José M; van Straaten, Elizabeth C W; Scheltens, Philip; Barkhof, Frederik; et al.
Abstract : Background: Previous research has indicated that corpus callosum atrophy is associated with global cognitive decline in neurodegenerative diseases, but few studies have investigated specific cognitive functions. Objective: To investigate the role of regional corpus callosum atrophy in mental speed, attention and executive functions in subjects with age-related white matter hyperintensities (WMH). Methods: In the Leukoaraiosis and Disability Study, 567 subjects with age-related WMH were examined with a detailed neuropsychological assessment and quantitative magnetic resonance imaging. The relationships of the total corpus callosum area and its subregions with cognitive performance were analysed using multiple linear regression, controlling for volume of WMH and other confounding factors. Results: Atrophy of the total corpus callosum area was associated with poor performance in tests assessing speed of mental processing—namely, trail making A and Stroop test parts I and II. Anterior, but not posterior, corpus callosum atrophy was associated with deficits of attention and executive functions as reflected by the symbol digit modalities and digit cancellation tests, as well as by the subtraction scores in the trail making and Stroop tests. Furthermore, semantic verbal fluency was related to the total corpus callosum area and the isthmus subregion. Conclusions: Corpus callosum atrophy seems to contribute to cognitive decline independently of age, education, coexisting WMH and stroke. Anterior corpus callosum atrophy is related to the frontal-lobe-mediated executive functions and attention, whereas overall corpus callosum atrophy is associated with the slowing of processing speed.